(untitled) (Research, Society and Development, 2024)
The objective of this study was to review the literature on the perception of lay adults regarding the importance of primary teeth, considering the sociodemographic profile and knowledge of preventive care for teeth. To answer the question, searches were carried out in the PubMed and BVS databases, in the period between January and February 2024, using the MeSH terms “Deciduous dentition”, “beliefs”, “myths” and “attitude” associated to the Boolean operators AND and OR. Studies that answered the guiding question, involving lay adults and published in the last 5 years were included. The initial searches resulted in 49 articles. After screening and applying the eligibility criteria, the final sample comprised 14 studies. Most of the studies were published in India and Saudi Arabia, between 2019 and 2024, and the perception of parents or guardians of children, pregnant women and midwives was assessed through questionnaires. Adults’ knowledge about oral health is limited and directly influences the health of primary teeth and children’s oral hygiene habits, but in general they recognize the importance of primary teeth. The sociodemographic profile has a broad influence on this aspect, therefore, those responsible with a higher level of education and a greater number of children have better levels of perception regarding the importance. People with lower levels of education are the most affected with little information. Furthermore, it was noticed that lay adults understand the importance of preventive care for good oral health.